A Study on the Seismic Performance of Steel H-Column and T-Beam-Bolted Joints - Hongtao Ju; Wen Jiang; Xuegang Hu; Kai Zhang; Yan Guo; Junfen Yang; Kaili Hao (Applied Sciences)
The finite-element model was developed using ABAQUS to investigate the hysteretic properties of space joints. This study examined the effects of axial compression ratio, T-plate stiffness, column wall thickness, and bolt-preload on the joint’s hysteretic behavior. The model was verified by comparing the failure modes, hysteresis curves, and skeleton curves of the specimens with the test results of the relevant literature, ensuring the reliability of the research. The results reveal three primary failure modes: beam flange buckling, T-plate buckling, and column-wall buckling; increasing the thickness of the T-plate web or column wall significantly enhances joint stiffness and mitigates brittle failure. Specifically, the stiffness of T-plate 1 has a substantial impact on joint performance, and it is recommended that its web thickness be no less than 18 mm. In contrast, variations in the thickness of T-plate 2 have negligible effects on seismic performance. Increasing the column wall thickness improves the bearing capacity and stiffness of the joint, with a recommended minimum thickness of 12 mm, which should not be less than the flange thickness of the steel beam. While an increase in the axial compression ratio reduces the bearing capacity and stiffness, it enhances the energy dissipation capacity and ductility of the joint. Notably, variations in bolt-preload were found to have minimal influence on joint performance. These findings provide valuable insights for optimizing the design of unilateral bolted joints in steel structures to improve seismic resilience.